Parking 2.0. - Willie D. Jones
A host of new smart parking technologies are helping municipalities meet their twin aims of collecting revenue for city services and preventing a small number of cars from monopolizing a limited number of parking slots. These advances are also benefiting motorists by making the tasks of finding a space and paying to park less of a hassle. Some examples include the solar-powered smart meters which allow drivers to pay for parking with coins, credit or debit cards, or smart cards preloaded with money, and the use of wireless communications to let drivers pay for parking in advance, reserve a space, or add additional time from wherever they are. Other innovations allow drivers to use their personal computers or cellphones to select and reserve parking slots well in advance
Keywords: Cellphones; Parking slots; Personal computers; Revenue collection; Smart parking technologies; Solar-powered smart meters; Wireless communications